PANDANGAN PEGAWAI BKKBN WILAYAH D.I.YOGYAKARTA TERHADAP UU NO. 16 TAHUN 2019 TERKAIT BATAS USIA MENIKAH - Afifah Amini (Media Bina Ilmiah, 2025)
The Marriage Law states that marriage can take place if the man has reached the age of 19 years and the woman is 19 years old. Apart from that, applicants who are less than the legal age can apply for a dispensation at the Religious Court. On the other hand,there are regulations from the National Population and Family Planning Agency (BKKBN) which recommend that the ideal marriage age be at a mature age, namely 21 years for women and 25 years for men. This research is included in the field research category and is descriptive-analytic in nature. Data collection techniques use interview and documentation methods. Based on research conducted by the author at the BKKBN D.I. Yogyakarta Region in looking at Law Number 16 of 2019, it can be concluded that the BKKBN supports increasing the marriage age from 16 years for women to 19 years for men and women. However, the BKKBN also has an ideal age for marriage which is still being disseminated continuously today. The efforts that have been made by the BKKBN in determining the ideal age for marriage are based on several aspects, namely; health, economic, psychological, educational and population aspects. The ideal age according to the BKKBN is also considered to have benefits for human life, especially for married couples. If seen from the perspective of Maqasid al- shari'ah, the most important thing in this program is related to hifdh nasl, part of the five elements of maqāşid